Optimizing the Use of Deceased Donor Kidneys at Risk of Discard: A Clinical Practice Guideline - Joanna C. Dionne; Joanna C. Dionne; Joanna C. Dionne; Patricia Campbell; Héloïse Cardinal; Héloïse Cardinal; Tatiana Giannidis; Aviva Goldberg; S. Joseph Kim; S. Joseph Kim; Greg Knoll; Michel Pâquet; et al. (Transplant International)
Underutilization of deceased donor organs has worsened the gap in the number of kidneys available for transplantation. The purpose of this clinical practice guideline is to provide recommendations on the utilization of donor kidneys at risk of discard. Six conditional recommendations were made all with very low certainty of evidence: 1) We suggest utilizing extended criteria donor (ECD) kidneys for transplantation rather than remaining on the wait list and continuing with dialysis; 2) We suggest utilizing kidneys from ECD versus non-ECD in selected transplant candidates; 3) We suggest that organs from older kidney donors can be used in selected transplant candidates who may derive benefit from them; 4) We suggest that kidneys from deceased donors with acute kidney injury can be used for transplantation based on clinician assessment and donor factors; 5) We suggest that donor kidneys with acute kidney injury from either ECD or non-ECD be used for kidney transplantation; 6) We suggest using kidneys from donors after death determination by circulatory criteria for transplantation. This clinical practice guideline provides evidence for the use of deceased donor kidneys that are at risk of discard and may improve the shared decision-making between transplant physicians and wait-listed patients.